Analisis Pragmatik dan Persuasi dalam Iklan "Buanglah Sampah pada Tempatnya Bumi Bukan Tempat Sampahmu" - Novriana A.S Sitanggang; Syafrina Ulfa (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to analyze the pragmatic aspects and persuasive strategies in a public service advertisement entitled "Throw Trash in Its Place. The Earth is Not Your Trash Can." This study uses a pragmatic approach with a focus on the theory of speech acts, implicature, deixis, and politeness of language to reveal how to convey messages effectively and persuasively in the context of public communication. The advertisement is analyzed as a form of directive communication that aims to encourage changes in people's behavior towards issues of cleanliness and environmental concern. The results of the analysis show that this advertisement utilizes strong but polite directive speech acts, normative implicatures to instill values, the use of personal deixis to build closeness with the audience, and positive and negative politeness strategies to maintain social relations. Thus, advertisements not only function as a medium for conveying information, but also as an instrument for forming collective awareness through a communicative approach that is contextual, efficient, and emotionally and rationally appealing to its audience.